The effects of cognitive, physical, and somatosensory rehabilitation after right temporo-parietal tumor resection on cognitive, motor, somatosensory, and electrophysiological parameters: A case report. - Saricaoglu, Mevhibe; Hanoglu, Lutfu; Guntekin, Bahar; Ozkara, Cigdem (Physiotherapy Theory & Practice, 2023)
This report examines the effects of a multimodal rehabilitation program which includes cognitive, physical, and somatosensory rehabilitation after right temporo-parietal tumor resection on cognitive, motor, somatosensory, and electrophysiological parameters. A 22-year-old patient presented with sensory loss in the dominant left hand and reduced writing ability after right temporo-parietal lobe resection. Cognitive, motor, and sensory evaluations were carried out pre and post-treatment. The patient's spontaneous electroencephalo-gram (EEG) and an EEG during application of transcutaneous electrical nerve stimulation (TENS) (TENS EEG) were recorded. As a reference for the patient's electrophysiological values, EEGs of 4 healthy individuals were also taken. Over a period of 1 year, the patient received multimodal rehabilitation which includes cognitive, physical, and somato-sensory rehabilitation on 2 days each week. An improvement of the patient's cognitive capacities, motor strength, superficial, deep and cortical sensations was achieved. After rehabilitation, an increase in parietal and occipital alpha activity as well as in frontal and parietal beta activity was seen both in spontaneous EEG and in TENS EEG. With increasing TENS intensity, alpha and beta power increased as well. Our findings suggest that a multimodal rehabilitation program may improve cognitive, sensory, and motor effects after resection due to tumor surgery.